The effects of a nutritional supplement containing salacinol in neonatal Thoroughbred foals - IIDA, Atsushi (J Equine Sci, 2020)
A nutritional supplement containing salacinol (NSS) was administered to Thoroughbred foals daily beginning 21 days after birth, and clinical signs and intestinal microbiota were analyzed. The average number of days for which foals exhibited a fever between 21 and 110 days after birth was determined. The number of days was significantly reduced, by approximately 1/3, in the NSS group compared with the control group. Furthermore, improved weight gain was observed in the NSS group compared with the control group. By analyzing the intestinal microbiota, it was determined that the ratio of Clostridium cluster XIVa increased after 3 weeks of NSS administration. These results demonstrate that the daily administration of NSS might improve the intestinal environment of neonatal foals and be useful for health.